Investing sustainably in African livestock development: Opportunities and trade-offs - Carlos Seré (University of Bonn, Center for Development Research (ZEF), 2020)
The production and consumption of animal source foods is central to the ongoing discussion of global food systems. The objectives of this report are first to describe the patterns and changing structures of the Sub-Saharan Africa (SSA) livestock sector and secondly to explore innovations that can help to address the complex trade-offs involved in investing in the development of a sustainable livestock sector. The report reviews trends in consumption, production and trade of major livestock commodities and feed in the four subregions of SSA and presents an overview of key issues facing the sector. A scenario for the SSA livestock sector in 2030 is developed using the IMPACT model. It shows significant growth of production across all major livestock commodities with poultry and pork growing faster than ruminant meat production. A series of technical and institutional innovations show opportunities to address the challenges of sustainably intensifying livestock production in SSA. They include improved forages, improved fodder conservation, artificial insemination combined with estrus synchronization, intensive beekeeping, livestock masterplans, livestock asset transfer programs, indexbased livestock insurance and livestock market information systems. The report concludes that livestock plays multiple key roles in the food systems in SSA and will continue to do so in the coming years. The complexity of the system and the multiple trade-offs imply a need for policy makers to shift from frequent "benign neglect" to actively invest in the analytical capacity to understand the changing roles and issues in SSA livestock development. In spite of important divergences on the future role, opportunities and risks associated with livestock production and consumption, developed economies and SSA nations will benefit from international scientific cooperation to jointly tackle the complex issues facing livestock production as part of the envisaged global food system.
Keywords: O13; O30; O33; Q16; Q18; 330; livestock; Sub-Saharan Africa; production systems; climate change; food systems; technicaland institutional innovations; ruminants; monogastrics; scenario 2030